A history of Argentina in the twentieth century - Romero, Luis Alberto (Pennsylvania State University Press, 2002)
This text is a reflection on the "Argentine dilemma" and the challenges that the country faces as it tries to rebuild democracy. The author painstakingly reconstructs and analyzes Argentina's modern history, from the "alluvial society" born of mass immigration, to the dramatic years of Juan and Eva Perón, to the more recent period of military dictatorship and democracy. For this English-language edition, the author has also written a new chapter covering the decade of the 1990s.